(untitled) (jornal of the libyan geographical society, 2009)
The name of the Gulf of Sirte appeared under the name Greater Sirte, to distinguish it from another, smaller gulf, namely Lesser Sirte or the Gulf of Gabes. This indicates that something shared between them, despite the apparent difference in their characteristics: large and small, as the repetition of these prominent names suggests. It left its mark on historical geography, that these two water surfaces have distinctive features, the linguistic meaning of which resulted from its use as a description of any water surface, in which those characteristics are combined, which are known only to those who are knowledgeable about sea affairs and navigation, and this resulted in identifying the two gulfs and not others in the Mediterranean. Both are open bodies of water to the north and are wide, and therefore subject to strong winds that can cause significant disturbance to a huge body of water for several months each year.